Rastin partnership accounting part III: Instalment Financial Sharing (IFS) - Bijan Bidabad (Journal of Management and Science, 2023)
Purpose: This paper aims to explain a new system of accounting for partnership financing that applies in Rastin Profit and Loss Sharing Banking. In this system, the interest rate is not used in calculations and accounting; and instead, the "time value" of capital based on the amount and duration of the partnership is used. In this part, we will go to the details of removing Riba in instalment payments accounting details. Design: Rastin Partnership Accounting principles have been founded on off-balance-sheet items and on the basis of the institutions’ obligations to the depositors and receivers of financial resources, and they are in compliance with the nature of the intermediary financial activity (a partnership of depositor in the yields of the fund receiver via the bank). Findings: The distribution of profit among stakeholders (including workforce and capital owners) is accomplished according to the share of each beneficiary in the created value added. In this regard,Euler’s theorem, as the best mathematical-economic innovation for the distribution of income, is applied. Research limitations: This system is novel, and it is required to be more elaborated for further practical development and adjustment. Practical implications: In this accounting system, the return of the partnership is distributed among sharers based on the amount and duration of their partnership. The penalty for delay in payment is calculated from the amount of the incurred loss due to negligence or blameworthy of the undertaker and not upon a penalty interest rate. Social implications: Interest rate as an essential factor in conventional accounting is not usable in Islamic banking and other similar institutions that work based on partnership, such as mutual funds and saving and loan associations. The proposed system removes this shortage and is fairer than conventional accounting. Originality/value: The approach of this accounting system is fully different from conventional accounting because of the intrinsic characteristics of the intermediary role of financial partnership institutions and Islamic banks.